2020
DOI: 10.1111/ped.14232
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Ro/SSA antibody‐related atrioventricular block‐induced torsade de pointes

Abstract: Ro/SSA antibody, complete atrioventricular block, pacemaker implantation, QT prolongation, torsade de pointes. Congenital complete atrioventricular block (CAVB) is a rare but life-threatening disease. Most CAVB cases are caused by the transfer of maternal anti-Ro/SS-A antibody to the fetus through the placenta. Anti-Ro/SS-A antibody associated CAVB generally occurs in the neonatal period; however, it may occasionally occur later. Recently, it has been reported that anti-Ro/SS-A antibody contributes not only to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, there are some situations where the use of such therapeutic strategies leads to complicated issues. Mizuno et al reported an infant case of CAVB with TDP and no genetic evidence on LQTS of any variants in KCNQ1 , KCNH2 , or SCN5A [ 13 ]. In a study by Michaelsson et al, 7% of patients were identified to have prolonged QT intervals (corrected QT interval > 450 ms) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some situations where the use of such therapeutic strategies leads to complicated issues. Mizuno et al reported an infant case of CAVB with TDP and no genetic evidence on LQTS of any variants in KCNQ1 , KCNH2 , or SCN5A [ 13 ]. In a study by Michaelsson et al, 7% of patients were identified to have prolonged QT intervals (corrected QT interval > 450 ms) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AlTwajery et al ( 61 ) demonstrated that among 41 children affected with SLE, anti-Ro/SSA-positivity was associated with a higher prevalence of ECG abnormalities, particularly QTc prolongation > 450 ms. Finally, three cases of marked QTc prolongation complicated with ventricular tachycardia/TdP in infants from anti-Ro/SSA-positive mothers with aCHB are reported ( 63 65 ).…”
Section: Anti-ro/ssa-associated Long-qt Syndromementioning
confidence: 97%